2018
DOI: 10.1111/apm.12822
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in normal hematopoietic stem cells and leukemia

Abstract: Leukemia is developed following the abnormal proliferation of immature hematopoietic cells in the blood when hematopoietic stem cells lose the ability to turn into mature cells at different stages of maturation and differentiation. Leukemia initiating cells are specifically dependent upon the suppression of oxidative stress in the hypoglycemic bone marrow (BM) environment to be able to start their activities. Relevant literature was identified by a PubMed search (2000-2017) of English-language literature using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 93 publications
0
26
0
Order By: Relevance
“…BCR-ABL is probably one of the best examples of leukaemia-driving oncogenes; the expression of the chimeric BCR-ABL tyrosine kinase is sufficient for cell transformation in CML [ 114 ]. Several reports support the idea that BCR-ABL is able to induce ROS production from different sources, including mitochondria [ 115 ], the upregulation of NADPH oxidase activity [ 116 ] by increasing p47 Phox expression [ 117 ] and an enhanced glucose metabolism [ 118 ]. It seems that the increased ROS production would be important for cell growth and transformation.…”
Section: Oxidative Stress and Redox Signalling In Leukaemiamentioning
confidence: 98%
“…BCR-ABL is probably one of the best examples of leukaemia-driving oncogenes; the expression of the chimeric BCR-ABL tyrosine kinase is sufficient for cell transformation in CML [ 114 ]. Several reports support the idea that BCR-ABL is able to induce ROS production from different sources, including mitochondria [ 115 ], the upregulation of NADPH oxidase activity [ 116 ] by increasing p47 Phox expression [ 117 ] and an enhanced glucose metabolism [ 118 ]. It seems that the increased ROS production would be important for cell growth and transformation.…”
Section: Oxidative Stress and Redox Signalling In Leukaemiamentioning
confidence: 98%
“…It was reported that these cells are more sensitive to increases in ROS levels than the normal bone marrow cells. Therefore, increased ROS production or inhibition of the cellular antioxidant systems is increasingly considered as a therapeutic strategy to target the APCs [ 12 , 14 ]. In this study, we discovered that pretreatment of KG-1a CD34 + cells with the free radical scavenger NAC completely abrogated the DMAPE (or PepE)-mediated apoptosis, indicating that the apoptosis-inducing ability of DMAPE (or PepE) is attributed to its capability of promoting ROS production in APCs.…”
Section: Discussionmentioning
confidence: 99%
“…The unique features that render CD34 + AML cells as a potential risk factor of hematological malignancies are still under debate. Recent studies suggested that the aberrant regulation of signaling pathways such as ROS, NF-κB, Wnt/β-catenin, or Hedgehog pathway is critical to the pathogenesis of CD34 + AML cells [ [11] , [12] , [13] , [14] , [15] , [16] , [17] ]. The recovery of these signaling pathways could be used for the elimination of CD34 + AML cells.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the metabolism of HSCs, many regulatory mechanisms, including high antioxidant defense and a diversity of regulatory molecules, such as P53, FOXO3, Akt, MAPK, hypoxia inducible factor 1 (HIF-1) and ataxia telangiectasia mutated (ATM), are involved in maintaining the low ROS level of HSCs to protect HSCs from oxidative stress-induced injury [9][10][11][12][13] . Bone marrow stromal cells (BMSCs) residing in the HSC niche also has a vital role in maintaining the redox homeostasis of HSCs, and ROS in HSCs can be transferred to BMSCs, maintaining a low ROS level 14 .…”
Section: Hypoxia Is Significant For Maintaining the Biological Functimentioning
confidence: 99%
“…According to the literature, among various types of leukemia cells, including AML, chronic myeloid leukemia (CML) and promyelocytic leukemia cells, an increase in NOX activity is observed, indicating that NOX's constitutive activation is a very important source of intracellular ROS for LSCs [43][44][45] . Moreover, activated FMS-like tyrosine kinase and oncogenes such as BCR/ABL, cellular-myelocytomatosis viral oncogene and Ras are all closely related to changes in redox homeostasis in leukemic cells and increased ROS levels 9,46,47 . It has been found that antioxidant defense is decreased in different types of leukemia [48][49][50][51] , indicating that an imbalance between the oxidative and antioxidative systems may be one of the reasons for increased ROS levels in leukemic cells.…”
Section: Ros Levels Are Associated With the Status Of Leukemic Cellsmentioning
confidence: 99%